Software Reuse for Dynamic Systems in the Cloud and Beyond 14th International Conference on Software Reuse, ICSR 2015, Miami, FL, USA, January 4-6, 2015. Proceedings - Schaefer, Ina; Stamelos, Ioannis (Programming and Software Engineering,, 2014)
This book constitutes the refereed proceedings of the 14th International Conference on Software Reuse for Dynamic Systems in the Cloud and Beyond, ICSR 2015, held in Miami, FL, USA, in January 2015. The 21 revised full papers presented together with 3 revised short papers were carefully reviewed and selected from 60 submissions. The papers cover several software engineering areas where software reuse is important, such as software product lines, domain analysis, open source, components, cloud, quality.